Disposition to critical thinking, anxiety due to COVID-19 and academic self-efficacy in university students - Abanto-Ramirez, Carlos D.; Turpo-Chaparro, Josué E.; Apaza, Abel; López-Gonzales, Javier Linkolk (Frontiers in Education, 2024)
The present study aims to determine whether anxiety due to COVID-19 (AC) and disposition to critical thinking (DCT) predict academic self-efficacy (AS). The study is non-experimental, predictive, and cross-sectional. The sample was made up of 218 university students from northern Peru. The instruments used were the CAS, CTDS, and the EAPESA. The results showed that the AS was negatively and positively related to AC and DCT, respectively. AS in university students was significantly predicted by DCT (p<0.01), while AC was not a significant predictor (p>0.05). Strategies must be sought to improve and support this important aspect in each student to improve their disposition to critical thinking and academic self-efficacy. It is recommended for future studies to continue investigating variables associated with academic factors, such as those in this study, that lead to taking action for the effective development of university students.Following the emergence of a health emergency in the city of Wuhan (China) on December 31, 2019 (Organización Mundial de la Salud [OMS], 2020), the COVID-19 anxiety variable was coined, defined as the set of cognitive, psychological, emotional, and behavioral manifestations of anxiety produced by the information and social context experienced by Sars-cov2 (Lee, 2020). This anxiety was negatively related to coping with COVID-19 and general health (Yıldırım et al., 2021), depression, and panic buyingThe literature review was updated with the most recent studies related to the research topic. The gap in knowledge was identified, as well as the contribution of this research to the scientific community.